Rich democracies, poor people how politics explain poverty - Brady, David, 1972- (New York ; Oxford : Oxford University Press, 2009)
This book highlights that among affluent Western societies there is immense cross-national and historical variation in poverty, and seeks to determine what makes poverty so entrenched in some affluent democracies when it is a solvable problem in others.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Poverty; Poverty -- Government policy; Welfare state; Poverty -- Prevention